Students and terrorism: Study of Student Understanding Law No 5 of 2018 on Combatation of Criminal Acts of Terrorism in IAIN Surakarta - Lukman Harahap (Lembaga Penelitian dan Pengabdian Masyarakat, 2020)
This article aims to know in real student's understanding of Law No. 5 of year 2018 on combating criminal acts of terrorism. The data collection techniques used in this study use interviews, observations and documentation. Meanwhile the analysis used in this research is a qualitative descriptive. Simultaneous, planned and integrated aspects of prevention need to forward to minimize the occurrence of criminal acts of terrorism. The optimal prevention is done by involving ministries or related institutions as well as all components of the nation through the efforts of national preparedness, counter radicalisation, and deradicalisation coordinated by the National Management Agency Terrorism. To optimize the eradication of criminal acts of terrorism, it is necessary to strengthen institutional functions, especially the coordination functions held with the National Agency for Terrorism counter following its oversight mechanisms. While it relates to the eradication of criminal acts of terrorism in Indonesia is not merely a matter of law and law enforcement but it is also a social, cultural, economic problem closely related to the issue of national resilience So that policies and precautions and pemberantasannyapun are aimed at maintaining balance in the obligation to protect the sovereignty of the State, the rights of victims and witnesses, and the rights of suspects/defendants.